EEG Neurofeedback for ADHD: Double-Blind Sham-Controlled Randomized Pilot Feasibility Trial. (July 2013) - Arnold, L. Eugene; Lofthouse, Nicholas; Hersch, Sarah; Pan, Xueliang; Hurt, Elizabeth; Bates, Bethany; Kassouf, Kathleen; Moone, Stacey; Grantier, Cara
Objective: Preparing for a definitive randomized clinical trial (RCT) of neurofeedback (NF) for ADHD, this pilot trial explored feasibility of a double-blind, sham-controlled design and adherence/palatability/relative effect of two versus three treatments/week.Method: Unmedicated 6- to 12-year-olds with Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) ADHD were randomized to active NF versus sham-NF and to 2X versus 3X/week treatment frequency. Frequency switch was allowed after Treatment 24.Results: In two school years, 39 participants were recruited and 34 (87%) completed all 40 treatments. Child/parent guesses about assigned treatment were no better than chance. At Treatment 24, 38% chose 2X/week and 62% chose 3X/week. Both active NF and sham yielded large pre–post improvement on parent ratings but NF no more than sham.Conclusion: Blinding appears to work, and sham does not prevent recruitment/retention. Treatment frequency of 3X/week seems preferred over 2X/week and was as effective. A large double-blind RCT is feasible and necessary to test specific NF effectiveness.